PENGEMBANGAN MEDIA FLIPBOOK INTERAKTIF BERBASIS WEBSITE UNTUK MENINGKATKAN HASIL BELAJAR MUATAN PEMBELAJARAN IPAS MATERI GAYA SISWA KELAS IV SDN PAKINTELAN 01 KOTA SEMARANG - Munirah, Sa'idatum; Petra Kristi Mulyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aimed to develop interactive flipbook media to asses the validity and effectiveness of learning outcomes in the science curriculum for fourth-grade students at IV SDN Pakintelan 01, Kota Semarang. The study employed the Research and Development (R&D) method using ADDIE model encompassing five stages: Analyze, Design, Development, Implementation, and Evaluation. Data collection techniques included tests and non-tests methods such as interviews, observations, questionnaires, and documentation. Data analysis techniques involved media qualification analysis, response analysis from teachers and students, normality tests, t-tests, and n-gain. The flipbook validation results from the media experts were 92.72%, language validation was 96.67%, and content validation was 87.69%. Teacher responses averaged 97.16%, and student responses were 90.17%, all highly qualified categories. The effectiveness test results showed a significant difference between pretest and posttest scores, with a t-test sig (2-tailed) score of 0.00 < 0.05. The n-gain analysis indicated an improvementwith a medium criterion score  0.5677, or 56.77% demonstrating moderate effectiveness.